2017
DOI: 10.1371/journal.pone.0176123
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the utility of two gestural discomfort evaluation methods

Abstract: Evaluating physical discomfort of designed gestures is important for creating safe and usable gesture-based interaction systems; yet, gestural discomfort evaluation has not been extensively studied in HCI, and few evaluation methods seem currently available whose utility has been experimentally confirmed. To address this, this study empirically demonstrated the utility of the subjective rating method after a small number of gesture repetitions (a maximum of four repetitions) in evaluating designed gestures in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 65 publications
(61 reference statements)
0
4
0
Order By: Relevance
“…The LMC detects the positions of fine objects such as finger tips or pen tips in a Cartesian plane. Its interaction zone is an inverted cone of approximately 0.23 m³ and the motion detection range fluctuates between 20 mm and 600 mm [91,129]. The manufacturer reports an accuracy of 0.01 mm for fingertip detection, although 1 study showed an accuracy of 0.7 mm, which is considered superior to that achieved using MK [134,136].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The LMC detects the positions of fine objects such as finger tips or pen tips in a Cartesian plane. Its interaction zone is an inverted cone of approximately 0.23 m³ and the motion detection range fluctuates between 20 mm and 600 mm [91,129]. The manufacturer reports an accuracy of 0.01 mm for fingertip detection, although 1 study showed an accuracy of 0.7 mm, which is considered superior to that achieved using MK [134,136].…”
Section: Discussionmentioning
confidence: 99%
“…With regard to the LMC, once the 6 studies on robotics had been discarded, 4 articles were identified that presented limitations derived from using the device (18%). These studies noted alterations in performance when there was dirt on the surface of the device, as well as the limited number of gestures recognized owing to the occlusion phenomenon [87], alterations caused by ambient lighting [129], fatigue in some users [90], and a lack of studies validating the device for medical use [77].…”
Section: Discussionmentioning
confidence: 99%
“…One study used RULA in conjunction with another method called Quick Rating (QRating) to ergonomically assess people who made typical gestures when communicating. Physical discomfort during these gestures should be controlled [243].…”
Section: • Gesturesmentioning
confidence: 99%
“…These include subjective psycho-physical ratings such as the Borg CR10 (N. Williams, 2017) and objective kinematics-based scoring systems such as the Rapid Upper Limb Assessment (RULA) (McAtamney & Corlett, 2004). The Borg CR10 and RULA, assessed after a short number of gesture repetitions, have both been shown to be useful for predicting discomfort and fatigue resulting from actual prolonged and repetitive gesture use (Son et al, 2017). Strategies for mitigating performance bias include the use of covert kinaesthetic priming (Hoff et al, 2016) and soft constraints such as attaching weights to participants' wrists (Ruiz & Vogel, 2015).…”
Section: Introductionmentioning
confidence: 99%